A Flexible Array for Cardiac 31P MR Spectroscopy at 7 T - Roat, Sigrun; Vít, Martin; Wampl, Stefan; Schmid, Albrecht Ingo; Laistler, Elmar (Frontiers in Physics, 2020)
Purpose: The simulation optimization and implementation of a flexible 31P transmit/receive coil array, under the geometrical constraint of fitting into the housing of an already existing 12-channel proton array, to enable localized cardiac 31P MRS at 7 T is presented. Methods: The performance in terms of homogeneity, power and SAR efficiency, and receive benchmark of 32 potential array designs was compared by full wave 3D electromagnetic simulation considering the respective optimal static B1+ shims. The design with the best performance was built and compared to a commercially available single loop in simulation and measurement. Results: Simulation revealed an optimal array design comprising three overlapping elements, each sized 94 × 141 mm2. Simulation comparison with a single loop coil predicted a performance increase due to increased power efficiency and lower SAR values. This was verified by phantom measurements, where an SNR increase of 46% could be observed for localized 31P spectroscopy in a voxel positioned comparable to an in vivo cardiac measurement scenario. Conclusion: A flexible 31P/1H RF coil array with improved SNR is presented, enabling localized in vivo cardiac 31P spectroscopy at 7 T.